Analysis of TPACK Content in the Curriculum of Educational Study Programs in Higher Education - Solihin, Rahmat (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to analyze the structure and depth of Technological Pedagogical Content Knowledge (TPACK) content in higher education curriculum documents, with a case study at the Faculty of Tarbiyah, Institut Asy-Syukriyyah, consisting of the Primary School Teacher Education (PGMI) and Islamic Education (PAI) Study Programs. The research focuses on how the curricula of the two study programs include aspects of content knowledge (CK), pedagogical knowledge (PK), technological knowledge (TK), and their integration within the TPACK framework. This research uses a qualitative descriptive approach, using document analysis, interviews, and observation as data collection techniques. Data were collected from curriculum documents used in the 2024-2025 academic year at the Faculty of Tarbiyah, especially the PGMI and PAI Study Programs. Interviews were conducted with the dean of the Tarbiyah Faculty, the heads of the PAI and PGMI study programs, two lecturers, and two students, as well as observations of lecture implementation in the same academic year. The data were analyzed using qualitative methods validated through source and technique triangulation, then interpreted based on the seven TPACK components. The results show that the curricula of both study programs meet national standards, aligning graduate profiles, learning outcomes, courses, and semester learning plans (RPS). The depth of CK and PK emerges as the main strengths: PGMI emphasizes multidisciplinary content and basic teaching strategies, while PAI emphasizes mastery of Islamic sciences and teaching methodology. Meanwhile, TK and TPACK integration remain limited, mainly appearing as the use of simple digital media and online learning systems. Integration at the levels of PCK, TCK, TPK, and TPACK is still partial and not yet systematically embedded in the curriculum. This study implies that strengthening TPACK integration in curriculum design is essential to better prepare pre-service teachers for the digital era. Future research could expand the analysis to a broader range of teacher education programs in Indonesia, and further examine the effectiveness of TPACK-based curriculum interventions in improving teaching competence and student learning outcomes.